Reaksi Pasar Modal Terhadap Perisitiwa Penetapan Tersangka Baru Korupsi Tambang Timah PT. Tins (Studi Kasus Pada Saham Perusahaan Pertambangan) - Al-Kautsar, Ziyad; Hudaya, Robith (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to test and explain whether there is a capital market reaction to the announcement of the stipulation of a new suspect in tin mining corruption in the mining sector on the Indonesia Stock Exchange (IDX) for 2024. This study has a population of 74 companies engaged in mining, And there are also 61 company samples with an observation period of 15 days. This study uses a quantitative approach using an event study which is a special method for analyzing certain events that are believed to have an impact or reaction. The focus of this study is to see the reactions indicated by changes in Average Abnormal Return and Trading Volume Activity using the One Sample Kolmogorov-Smirnov test to conduct a normality test and paired sample T-test if the data has been normally distributed. Then use the Wilcoxon Signed Rank Test test if the data is not normally distributed. The results of this study indicate that there is no average abnormal return but has a significant average trade volume of activity before and after the announcement of the stipulation of new suspects in the corruption of PT. Tin (tins). This research contributes to seeing how the capital market responds to the announcement of the new suspect PT. Tin (tins), as well as the extent to which this event affects investors through abnormal return and trading volume activity.